Reliability of internal column-slab connection under punching according to NBR 6118:2014 - SILVA,G. R. (2018)
Abstract This article presents a study on the reliability of internal column-slab connection under punching, designed according to the Brazilian Standard NBR 6118:2014. The evaluation of reliability was made by comparing the reliability index β with the target reliability index recommended by the fib Model Code 2010. The reliability indexes were calculated through statistical analysis of the data obtained with numerical simulations using the Monte Carlo method, with Latin Hypercube sample, through ANSYS software. The results showed that, for most slabs, the indexes of reliability β presented satisfactory results. However, some of the tested slabs presented results below the assumed limits. Therefore, this article suggests that the Brazilian Standard NBR 6118:2014 is appropriate for most flat slabs without shear reinforcement.